Comparison of middle latency responses in presbycusis patients with two different speech recognition scores - (:unkn) unknown (ELSEVIER SCI LTD, 2007)
Objective: The purpose of this study is to evaluate whether the middle latency responses (MLR) can be used for an objective differentiation of patients with presbycusis having relatively good (Group I) and relatively poor speech recognition scores (Group II). Methods: All the participants of these groups had high frequency down-sloping hearing loss with an average of 26-60 dB HL. Data were collected from two described study groups and a control group, using pure tone audiometry, monosyllabic phonetically balanced word and synthetic sentence identification, as well as NILR. The study groups were compared with the control group. Results: When patients in Group I were compared with the control group, only ipsilateral Na latency of middle latency evoked response was statistically significant in the right ear whereas ipsilateral Na latency in the right ear, ipsilateral and contralateral Na latency in the left ear of the patients in Group II were statistically significant. Conclusion: Thus, as an objective complementary tool for the evaluation of the speech perception ability of the patients with presbycusis, Na latency of MLR may be used in combination with the speech discrimination tests. (c) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: presbycusis; speech recognition score; auditory middle latency response